2017
DOI: 10.1016/j.atherosclerosis.2017.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Environmental tobacco smoke and peripheral arterial disease: A review

Abstract: An association between exposure to environmental tobacco smoke and development of peripheral arterial disease or clinically significant arterial injury in non-smokers is supported by moderate quality evidence in the literature. Larger, longitudinal observational studies addressing current limitations, including sources of bias, inconsistency and imprecision, are needed to provide more robust and consistent evidence. Regardless, evidence of potential detrimental impacts supports ongoing restrictions on freedom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 50 publications
(86 reference statements)
0
12
0
2
Order By: Relevance
“…Meanwhile, compared with never smokers, current and former smokers with PAD had higher rates of death ( 37 ). High exposure to environmental tobacco also increased the risk of PAD among non-smokers ( 38 ). We found that the percentage contribution of tobacco use to age-standardized death of PAD was much larger in males than in females, which is consistent with the findings from Kumakura et al ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, compared with never smokers, current and former smokers with PAD had higher rates of death ( 37 ). High exposure to environmental tobacco also increased the risk of PAD among non-smokers ( 38 ). We found that the percentage contribution of tobacco use to age-standardized death of PAD was much larger in males than in females, which is consistent with the findings from Kumakura et al ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lo anterior está de acuerdo con el estudio UKPDS (30) en el que un buen control glucémico está asociado con disminución del riesgo de complicaciones macrovasculares; de igual manera una revisión sistemática y metaanálisis de la Universidad de Berna encontró que un mejor control glucémico en pacientes con DM1 y DM2 se asocia con una disminución de la incidencia de eventos macrovasculares especialmente EAP y accidentes cerebrovasculares (31). El consumo de cigarrillo estuvo presente en los pacientes con EAP, no se indagó por la intensidad ni duración del consumo pero se ha encontrado que la prevalencia e incidencia de EAP es mayor en pacientes con alto consumo de tabaco y tiempo prolongado de exposición (32)(33)(34)(35). La mayoría de los pacientes con EAP tenían un IMC > 25.…”
Section: Discussionunclassified
“…A risk factor for atherosclerotic disease that was significantly different between the two HF groups was smoking, being more prevalent in the HFpEF population (26%x16%, p =0.001). This factor is cited as associated with the risk of PAD in several studies and may have contributed to the high rates of diagnosis of PAD in both populations, although mainly in patients with HFpEF (21,22).…”
Section: Discussionmentioning
confidence: 99%